Analisis Yuridis terhadap Putusan Pengadilan dalam Pencatatan Perkawinan Beda Agama Sebelum dan Sesudah Adanya SEMA No. 2 Tahun 2023 : Studi Kasus Putusan nomor 91/Pdt.P//2022/PN Bks - Reynold Simandjuntak; Zahwa A. Alhabsyi; Grace L. D. Lingga; Ika Syafitri Pakaya; Aisa Yulia M Sabir; Gabriel Leon Wulung; Virgilio Wando Lelewa (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Interfaith marriages often experience difficulties in official registration, which has an impact on legal status and civil rights. In the Constitutional Court Decision Number 68/PUU/XII/2014, it firmly rejected interfaith marriages, this decision emphasized that interfaith marriages have no constitutional basis in Indonesia and are still regulated by applicable laws. This study aims to analyze court decisions relating to applications for registration of marriages between adherents of different religions, especially before and after the issuance of SEMA No. 2 of 2023. This study uses a normative research method and a case study approach to decision number 91/Pdt.P//2022/PN Bks. This study attempts to answer questions related to the registration of interfaith marriages